Mitochondrial respiratory capacities are not linked to individual variation in hypoxia tolerance and standard metabolic rate in European seabass Dicentrarchus labrax - Elisa Thoral; Julie Nati; Jean‐Baptiste Quémeneur; Léann Lozac'h; Germain Salou; Alain Vergnet; Mathieu Besson; Marc Vandeputte; François Allal; Karine Salin; David J. McKenzie; Loïc Teulier (Journal of Fish Biology, 2026)
In hypoxic environments, fish attempt to regulate their metabolic rate as oxygen levels in the water decline. Individuals that have low energy requirements for maintenance – standard metabolic rate (SMR) – are expected to have higher hypoxia tolerance, measured as the critical water oxygen saturation threshold (S crit ) below which they cannot regulate SMR. These whole animal traits may, in turn, be linked to aspects of individual mitochondrial oxidative metabolism that underpin SMR. We therefore investigated, in European seabass Dicentrarchus labrax , whether inter‐individual variation in SMR and S crit , measured by whole animal respirometry, was correlated with elements of mitochondrial metabolism in liver and heart, measured by high resolution respirometry (HRR). Among the 96 fish studied, inter‐individual variation in S crit was dependent upon variation in SMR. However, there was no evidence for correlations between SMR or S crit and individual mitochondrial respiratory capacities. Our results indicate that individual variation in complex whole animal traits of respiratory metabolism cannot always be linked to variation in subcellular mitochondrial phenotypes.

Lithium isotopes in waters of the tropical volcanic island of Guadeloupe: A proxy of high and low-temperature water-rock interactions - Céline Dessert; Mathieu Dellinger; Clémentine Clergue; Jérôme Gaillardet; Marc F. Benedetti (Geochimica et Cosmochimica Acta, 2026)

Environmental consequences of genetic improvement of growth and fillet yield in gilthead seabream: A life cycle assessment from breeding to plate - Sophie De Montmorillon; Simon Pouil; Marc Vandeputte; Jean-Sébastien Bruant; Jérôme Bugeon; Ivonne Acosta-Alba; Cédric Pincent; Benjamin Quittet; Mathieu Besson; Joël Aubin; Pierrick Haffray (Aquaculture, 2026)

Soil structure assessment using pedomorphological descriptors – SSAPD in Quebec - Eduardo Chavez Benalcazar; Marc-Olivier Gasser; Jacynthe Dessureault-Rompré; Gi-Mick Wu; Jean-Benoît Mathieu; Catherine Bossé (Soil and Tillage Research, 2026)

Integration of the exposome concept into health risk assessments: a challenge for health safety agencies - Amélie Crépet; Philippe Quénel; Jeanne Garric; Alain Kaufmann; Jean-Marc Bonmatin; Pascale Duché; Aurélie Mathieu; Madeline Carsique; Julien Jean; Pascal Sanders; Jean-Pierre Cravedi; Matthieu Schuler; et al. (Environmental Research, 2025)

Adaptive Challenges of Past and Future Invasion of Drosophila suzukii : Insights From Novel Genomic Resources and Statistical Methods Combining Individual and Pool Sequencing Data - Louise Camus; Nicolas O. Rode; Svitlana Serga; Anne Loiseau; Xiao Chen; Carole Iampietro; Marc Kenis; William Marande; Julián Mensch; Hugues Parinello; Marija Savić Veselinović; Sophie Valière; et al. (Molecular Ecology, 2025)
Global change is accelerating biological invasions, making it crucial to understand how species adapt in new environments to improve management strategies. Genomic data provide valuable insights into adaptation through genotype‐environment association (GEA) studies, which identify genes and biological processes tied to invasion success, and through geometric genomic offset (gGO) statistics, which estimate genetic (mal)adaptation to new environments. Here, we investigate genetic adaptation in the invasive pest Drosophila suzukii using novel genomic resources and statistical methods. We use a new chromosome‐level genome assembly and data from 37 populations, combining publicly available and newly generated pooled and individual sequencing data, analysed with an enhanced version of BayPass software, tailored for such hybrid datasets. First, we identify genomic regions showing genetic differentiation between native and invasive populations. Then, using a GEA with 29 environmental covariates, we estimate the gGO between the source environments and the invaded areas, shedding light on the potential adaptive challenges D. suzukii faced during previous invasions. In addition, we estimate gGO for geographical areas not yet invaded to predict future invasion risks, and identify regions from which preadapted populations may originate. Our results reveal numerous genomic regions associated with the invasive status from genome scans. However, when considering broader patterns of adaptation to specific environmental variables through gGO analyses, we find that D. suzukii populations likely faced only limited adaptive challenges across their major invasion range, while certain uninvaded regions still remain at high risk of future invasion. Our study offers significant insights into D. suzukii adaptation and provides a practical population genomics framework to predict biological invasions, applicable to various species.

The broadband light analyzer of complex aerosol: characterization and first applications - Tommaso Isolabella; Marco Brunoldi; Federico Mazzei; Franco Parodi; Paolo Prati; Virginia Vernocchi; Vera Bernardoni; Gianluigi Valli; Roberta Vecchi; Paola Formenti; Clarissa Baldo; Mathieu Cazaunau; et al. (Atmospheric Environment, 2025)

Management of invasive candidiasis in French ICUs: insights from a 2024 nationwide survey - Mathieu Esposito; Florent Lemery; Nelly Agrinier; Marc Soudant; Alexandre Charmillon; Nicolas Degand; Joséphine Dorin; Jean Dellamonica; Lucas Morand; Claire Roger; Julien Scala-Bertola; Marc Leone; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Corrigendum to “Genomic selection for individual feed efficiency in the European seabass: Response to selection on efficiency, commercial traits and sex” [Aquaculture Volume 595, Part 2, 30 January 2025, 741682]. - François Allal; Mathieu Besson; Emilie Delpuech; Chloé Barrier-Loiseau; Alain Vergnet; Franck Morell; Marie-Odile Blanc; Stéphane Lallement; Frédéric Clota; François Ruelle; Marc Vandeputte (Aquaculture, 2025)

Combining acoustic telemetry with archival tagging to investigate the spatial dynamic of the understudied pollack, Pollachius pollachius - Marine Gonse; Martial Laurans; Justus Magin; Tina Odaka; Jean‐Marc Delouis; Stéphane Martin; François Garren; Coline Lazard; Mickael Drogou; Thomas Stamp; Peter Davies; Alice Hall; et al. (Journal of Fish Biology, 2025)
Combining fish tracking methods is a promising way of leveraging the strengths of each approach while mitigating their individual weaknesses. Acoustic telemetry provides presence information as the fish move within receiver range, eliminating the need for tag recovery. Archival tags, on the other hand, record environmental variables on tag retrieval, enabling continuous path reconstruction of a fish beyond coastal regions. This study capitalizes on the combination of both methods for geolocating pollack, Pollachius pollachius , an understudied species of the northeast Atlantic, where declining stocks are raising concern. Essential knowledge of population structure and connectivity between essential habitats is critically lacking and could help inform stock assessment and management. The aims of the study were (1) to evaluate the feasibility of double‐tagging pollack, known for being challenging to tag, and (2) to track seasonal movements across the Channel to gain first insights into pollack spatial ecology. In 2022, an extensive network of acoustic receivers was been deployed in the Channel along the French, English, and Belgian coasts as part of the Fish Intel project. We tagged 83 pollack with acoustic transmitters, among which 48 were double‐tagged with data storage tags. Post‐tagging survival assessment, conducted on a subset of 35 individuals, revealed a successful procedure with a 97% short‐term survival rate. By October 2023, the acoustic telemetry network detected 30 out of 83 pollack at least once, with no large‐scale movements observed across the Channel. Presence in the network fluctuates seasonally, peaking in summer, particularly among immature fish. Integrating acoustic detections with temperature and depth time series in a geolocation model enabled trajectory reconstruction of 10 recaptured pollack, seven of which were detected by the network. This combined tracking approach revealed coastal movements along the coast of Brittany in France, highlighting the ecological significance of the Iroise Sea for pollack throughout the year, particularly in summer. The geolocation model also suggested movements towards the entrance of the western Channel. This study highlights the complementarity of acoustic telemetry and archival tagging in reconstructing fish movements in their natural environment. As data accumulate, these innovative tracking methods promise to continually unveil new insights into the spatial ecology of the understudied pollack, which is essential for the species' management.

Enhancement of Agroecosystem Multifunctionality by Agroforestry: A Global Quantitative Summary - Antoine Mathieu; Marc‐Olivier Martin‐Guay; David Rivest (Global Change Biology, 2025)
In comparison with conventional agriculture, agroforestry systems improve the delivery of multiple ecosystem services and support greater biodiversity. Yet, the effects of agroforestry on various ecosystem services and biodiversity vary worldwide between climatic regions and system types, and studies often focus on measuring a small number of services or biodiversity indicators. We conducted a quantitative summary of multiple large‐scale meta‐analyses comparing service delivery or biodiversity between agroforestry systems and conventional agricultural systems to capture the global effect of agroforestry on agroecosystem multifunctionality. Data were aggregated from 20 meta‐analyses, many of them global, and response ratios were calculated to assess relative effects of agroforestry systems worldwide on multiple categories of biodiversity indicators and production, regulation, and support services. By combining different datasets that addressed specific ecosystem services or biodiversity indicators and analyzing 3075 comparisons between agroforestry systems and their conventional counterparts, we found that agroforestry enhanced ecosystem service delivery and biodiversity globally by an average of 23%. The effects were more pronounced on supporting and regulating services and biodiversity than on production services. The vast majority of analyzed services and biodiversity indicators were enhanced in agroforestry systems, while few were either not affected or affected negatively. Among ecosystem services analyzed along an aridity gradient, only soil organic carbon (SOC) stocks and forage production varied significantly. The positive effects of agroforestry on SOC stocks were stronger in drier conditions, while those on forage production followed a quadratic trend, with maximal benefits in arid conditions. Our results suggest that broad‐scale adoption of agroforestry in conventional agriculture could benefit agroecosystem multifunctionality globally without sacrificing productivity and would help support sustainable food production.

Plant Genetic Bases Associated With Microbiota Descriptors Shed Light Into a Novel Holobiont Generalist Genes Theory - Loeiz Maillet; Manon Norest; Adam Kautsky; Anna Geraci; Elisabetta Oddo; Angelo Troia; Anne‐Yvonne Guillerm‐Erckelboudt; Cyril Falentin; Mathieu Rousseau‐Gueutin; Anne‐Marie Chèvre; Benjamin Istace; Corinne Cruaud; et al. (Environmental Microbiology, 2025)
Plants as animals are associated with a cortege of microbes influencing their health, fitness and evolution. Scientists refer to all living organisms as holobionts, complex genetic units that coevolve simultaneously. This is what has been recently proposed as the hologenome theory. This exciting theory has important implications on animal and plant health; however, it still needs consistent proof to be validated. Indeed, holobionts are still poorly studied in their natural habitats where coevolution processes occur. Compared to animals, wild plant populations are an excellent model to explore the hologenome theory. These sessile holobionts have coevolved with their microbiota for decades, and natural selection and adaptive processes acting on wild plants are likely to regulate the plant–microbe interactions. Here, we conducted a microbiota survey, plant genome sequencing and genome–environmental analysis (GEA) of 26 natural populations of the plant species Brassica rapa . We collected plants over two seasons in Italy and France and analysed the root and rhizosphere microbiota. When conducting GEA, we evidenced neat peaks of association correlating with both fungal and bacterial microbiota. Surprisingly, we found 13 common genes between fungal and bacterial diversity descriptors that we referred to under the name of holobiont generalist genes (HGGs).

Muscle endurance, neuromuscular fatigability, and cognitive control during prolonged dual-task in people with chronic obstructive pulmonary disease: a case–control study - Cyril Chatain; Jean-Marc Vallier; Nicolas Paleiron; Fanny Cucchietti Waltz; Sofiane Ramdani; Mathieu Gruet (European Journal of Applied Physiology, 2025)
Purpose Recent studies suggest that, compared to healthy individuals, people with chronic obstructive pulmonary disease (pwCOPD) present a reduced capacity to perform cognitive-motor dual-task (CMDT). However, these studies were focused on short-duration CMDT offering limited insight to prolonged CMDT inducing fatigue, which can be encountered in daily life. The present study aimed to explore the effect of adding a cognitive task during repeated muscle contractions on muscle endurance, neuromuscular fatigability, and cognitive control in pwCOPD compared to healthy participants. Methods Thirteen pwCOPD and thirteen age- and sex-matched healthy participants performed submaximal isometric contractions of the knee extensors until exhaustion in two experimental sessions: (1) without cognitive task and (2) with a concurrent working memory task (i.e., 1-back task). Neuromuscular fatigability (as well as central and peripheral components measured by peripheral magnetic stimulation), cognitive performance, and perceived muscle fatigue were assessed throughout the fatiguing tasks. Results Independently to the experimental condition, pwCOPD exhibited lower muscle endurance compared to healthy participants ( p = 0.039), mainly explained by earlier peripheral fatigue and faster attainment of higher perceived muscle fatigue ( p < 0.05). However, neither effect of cognitive task ( p = 0.223) nor interaction effect (group × condition; p = 0.136) was revealed for muscle endurance. Interestingly, cognitive control was significantly reduced only in pwCOPD at the end of CMDT ( p < 0.015), suggesting greater difficulty for patients with dual tasking under fatigue. Conclusion These findings provide novel insights into how and why fatigue develops in COPD in dual-task context, offering a rationale for including such tasks in rehabilitation programs.

Genomic selection for individual feed efficiency in the European seabass: Response to selection on efficiency, commercial traits and sex - François Allal; Mathieu Besson; Emilie Delpuech; Chloé Barrier-Loiseau; Alain Vergnet; Franck Morell; Marie-Odile Blanc; Stéphane Lallement; Frédéric Clota; François Ruelle; Marc Vandeputte (Aquaculture, 2025)

PGE-Ni-Cu sulphide segregation by interaction of basaltic melt and peridotite xenoliths of the Catalan Volcanic Zone (Spain) - Miguel Roquet; Erwin Schettino; Marc Campeny; José María González-Jiménez; Michel Grégoire; Rubén Piña; Mathieu Leisen; Joaquín A. Proenza; Oscar Laurent; Llorenç Planagumà; Xavier Llovet (Lithos, 2024)

Can biochemical tracers reveal ontogenetic trophic shift and individual prey selection in white sharks from Guadalupe Island, Northeast Pacific? - Gaël Le Croizier; Mauricio Hoyos-Padilla; Felipe Amezcua-Martínez; Marc Aquino-Baleytó; Lucien Besnard; Fabienne Le Grand; François Le Loc'h; Margaux Mathieu-Resuge; Jean-Marie Munaron; Arthur Ory; Fany Sardenne; Gauthier Schaal; et al. (Environmental Research, 2024)

Ease and Limitations in Using Environmental DNA to Track the Spread of Invasive Host–Parasite Complexes: A Case Study of the Freshwater Fish Pseudorasbora parva and the Cryptic Fungal Parasite Sphaerothecum destruens - Théo Deremarque; Rodolphe Elie Gozlan; Ravo Ravaozafindrasoa; Giuliano Mucci; Lucie Delalex; Jean-Michel Foissy; Michaël Cagnant; Mathieu Clair; Justina Givens; Fabienne Justy; Alice Valentini; Delphine Nicolas; et al. (Fishes, 2024)
The spread of non-native species threatens biodiversity and exacerbates societal challenges like food security. To address this, effective conservation programs require detection methods that are easy to implement, accurate, and non-invasive. Over the past 15 years, environmental DNA (eDNA) techniques have gained popularity, surpassing traditional sampling methods. In this context, our study focused on tracking the invasive host–pathogen complex Pseudorasbora parva and Sphaerothecum destruens using eDNA metabarcoding. We collected water samples from freshwater canals over five months in the Camargue region, and once in Corsica Island, both in southern France. Total DNA was extracted from filtered water samples, and PCR-amplicons were sequenced using Illumina or Nanopore technologies. Our results revealed a high detection rate of P. parva in lentic ecosystems, aligning with habitat preferences of this small freshwater fish. Additionally, the detection rate in Camargue increased in May and June, likely due to the peak of the spawning season, which leads to more DNA being released into the environment (i.e., concentration and interaction of individuals). While eDNA successfully detected this invasive fish, we were unable to detect its cryptic fungal parasite, S. destruens, highlighting the challenges of identifying intracellular and cryptic fungal pathogens through eDNA methods.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Intraslab seismicity migration simultaneously with an interface slow slip event along the Ecuadorian subduction zone - Alexander Wickham-Piotrowski; Yvonne Font; Marc Regnier; Bertrand Delouis; Jean-Mathieu Nocquet; Louis De Barros; Virginie Durand; Quentin Bletery; Monica Segovia (Tectonophysics, 2024)

A quantitative weight-of-evidence method for confidence assessment of adverse outcome pathway networks: A case study on chemical-induced liver steatosis - Anouk Verhoeven; Jonas van Ertvelde; Joost Boeckmans; Alexandra Gatzios; Ramiro Jover; Birgitte Lindeman; Graciela Lopez-Soop; Robim M. Rodrigues; Anna Rapisarda; Julen Sanz-Serrano; Marth Stinckens; Sara Sepehri; et al. (Toxicology, 2024)

Above- and belowground carbon stocks under differing silvicultural scenarios - Anne Ola; William Devos; Mathieu Bouchard; Marc J. Mazerolle; Patricia Raymond; Alison D. Munson (Forest Ecology and Management, 2024)

Environmental exposure to metallic pollution impairs honey bee brain development and cognition - Coline Monchanin; Erwann Drujont; Gaël Le Roux; Philipp D. Lösel; Andrew B. Barron; Jean-Marc Devaud; Arnaud Elger; Mathieu Lihoreau (Journal of Hazardous Materials, 2024)

Demography of endangered juvenile green turtles in face of environmental changes: 10 years of capture-mark-recapture efforts in Martinique - Pierre Lelong; Aurélien Besnard; Marc Girondot; Caroline Habold; Fabienne Priam; Mathieu Giraudeau; Guillaume Le Loc'h; Aurélie Le Loc'h; Pascal Fournier; Christine Fournier-Chambrillon; Paco Bustamante; Sophie M. Dupont; et al. (Biological Conservation, 2024)

Organic UV absorbents in the deepwater redfish (Sebastes mentella) from the St. Lawrence Estuary and Gulf: Distribution and human health risk assessment - Fella Moualek; Mathieu Babin; Geneviève J. Parent; Dominic E. Ponton; Caroline Senay; Marc Amyot; Dominique Robert; Zhe Lu (Science of The Total Environment, 2024)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Spatial distribution and speciation of mercury in a recovering deepwater redfish (Sebastes mentella) population from St. Lawrence Estuary and Gulf, Canada - Fella Moualek; Dominic Belanger; Mathieu Babin; Geneviève J. Parent; Dominic E. Ponton; Marc Amyot; Caroline Senay; Dominique Robert; Zhe Lu (Environmental Pollution, 2023)

Forest adaptation strategies to reconcile timber production and carbon sequestration objectives under multiple risks of extreme drought and windstorm events - Sandrine Brèteau-Amores; Rasoul Yousefpour; Marc Hanewinkel; Mathieu Fortin (Ecological Economics, 2023)

A meta-analysis on wood trade flow modeling concepts - Valentin Mathieu; Jean-Marc Roda (Forest Policy and Economics, 2023)

Food for thought from French scientists for a revised EU Common Fisheries Policy to protect marine ecosystems and enhance fisheries performance - Hilaire Drouineau; Fabien Moullec; Didier Gascuel; Francis Laloë; Sterenn Lucas; Nicolas Bez; Patrice Guillotreau; Jérôme Guitton; Pierre-Yves Hernvann; Martin Huret; Sigrid Lehuta; Marc Léopold; et al. (Marine Policy, 2023)

Advancing fishery-independent stock assessments for the Norway lobster (Nephrops norvegicus) with new monitoring technologies - Jacopo Aguzzi; Damianos Chatzievangelou; Nathan J. Robinson; Nixon Bahamon; Alan Berry; Marc Carreras; Joan Batista Company; Corrado Costa; Joaquin del Rio Fernandez; Ahmad Falahzadeh; Spyros Fifas; Sascha Flögel; et al. (Frontiers in Marine Science, 2022)
The Norway lobster, Nephrops norvegicus , supports a key European fishery. Stock assessments for this species are mostly based on trawling and UnderWater TeleVision (UWTV) surveys. However, N. norvegicus are burrowing organisms and these survey methods are unable to sample or observe individuals in their burrows. To account for this, UWTV surveys generally assume that “1 burrow system = 1 animal”, due to the territorial behavior of N. norvegicus . Nevertheless, this assumption still requires in-situ validation. Here, we outline how to improve the accuracy of current stock assessments for N. norvegicus with novel ecological monitoring technologies, including: robotic fixed and mobile camera-platforms, telemetry, environmental DNA (eDNA), and Artificial Intelligence (AI). First, we outline the present status and threat for overexploitation in N. norvegicus stocks. Then, we discuss how the burrowing behavior of N. norvegicus biases current stock assessment methods. We propose that state-of-the-art stationary and mobile robotic platforms endowed with innovative sensors and complemented with AI tools could be used to count both animals and burrows systems in-situ , as well as to provide key insights into burrowing behavior. Next, we illustrate how multiparametric monitoring can be incorporated into assessments of physiology and burrowing behavior. Finally, we develop a flowchart for the appropriate treatment of multiparametric biological and environmental data required to improve current stock assessment methods.

Chemerin regulates normal angiogenesis and hypoxia-driven neovascularization - Cyrine Ben Dhaou; Kamel Mandi; Mickaël Frye; Angela Acheampong; Ayoub Radi; Benjamin De Becker; Mathieu Antoine; Nicolas Baeyens; Valérie Wittamer; Marc Parmentier (Angiogenesis, 2022)
Chemerin is a multifunctional protein initially characterized in our laboratory as a chemoattractant factor for leukocyte populations. Its main functional receptor is CMKLR1. We identified previously chemerin as an anti-tumoral factor inhibiting the vascularization of tumor grafts. We show here that overexpression of bioactive chemerin in mice results in a reduction of the density of the retinal vascular network during its development and in adults. Chemerin did not affect vascular sprouting during the post-natal development of the network, but rather promoted endothelial cell apoptosis and vessel pruning. This phenotype was reversed to normal in CMKLR1-deficient mice, demonstrating the role of this receptor. Chemerin inhibited also neoangiogenesis in a model of pathological proliferative retinopathy, and in response to hind-limb ischemia. Mechanistically, PTEN and FOXO1 antagonists could almost completely restore the density of the retinal vasculature, suggesting the involvement of the PI3-kinase/AKT pathway in the chemerin-induced vessel regression process.

Carotid Plaque Vulnerability Assessed by Combined Shear Wave Elastography and Ultrafast Doppler Compared to Histology - Guillaume Goudot; Jonas Sitruk; Anatole Jimenez; Pierre Julia; Lina Khider; Jean-Marc Alsac; Salma El Batti; Patrick Bruneval; Kisaki Amemyia; Olivier Pedreira; Hélène Mortelette; David Calvet; et al. (Translational Stroke Research, 2022)

An expert system for the conservation of Atlantic estuarine wet meadows: application to a Natura 2000 site in France - Mathieu Le Dez; Pauline Delbosc; Jan-Bernard Bouzillé; Marc Robin (Biodiversity and Conservation, 2021)

Accuracy of saliva and nasopharyngeal sampling for detection of SARS-CoV-2 in community screening: a multicentric cohort study - Solen Kernéis; Caroline Elie; Jacques Fourgeaud; Laure Choupeaux; Séverine Mercier Delarue; Marie-Laure Alby; Pierre Quentin; Juliette Pavie; Patricia Brazille; Marie Laure Néré; Marine Minier; Audrey Gabassi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

First characterization of congenital myasthenic syndrome type 5 in North Africa - Rochdi Khaoula; Mathieu Cerino; Nathalie Da Silva; Valerie Delague; Halima Nahili; Yamna Kriouile; Svetlana Gorokhova; Marc Bartoli; Rachid Saïle; Abdelhamid Barakat; Martin Krahn (Molecular Biology Reports, 2021)

Growth resistance and resilience of mixed silver fir and Norway spruce forests in central Europe: Contrasting responses to mild and severe droughts - Alessandra Bottero; David I. Forrester; Maxime Cailleret; Ulrich Kohnle; Arthur Gessler; Dominic Michel; Arun K. Bose; Jürgen Bauhus; Harald Bugmann; Matthias Cuntz; Loïc Gillerot; Marc Hanewinkel; et al. (Global Change Biology, 2021)
Extreme droughts are expected to increase in frequency and severity in many regions of the world, threatening multiple ecosystem services provided by forests. Effective strategies to adapt forests to such droughts require comprehensive information on the effects and importance of the factors influencing forest resistance and resilience. We used a unique combination of inventory and dendrochronological data from a long‐term (>30 years) silvicultural experiment in mixed silver fir and Norway spruce mountain forests along a temperature and precipitation gradient in southwestern Germany. We aimed at examining the mechanisms and forest stand characteristics underpinning the resistance and resilience to past mild and severe droughts. We found that (i) fir benefited from mild droughts and showed higher resistance (i.e., lower growth loss during drought) and resilience (i.e., faster return to pre‐drought growth levels) than spruce to all droughts; (ii) species identity determined mild drought responses while species interactions and management‐related factors strongly influenced the responses to severe droughts; (iii) intraspecific and interspecific interactions had contrasting effects on the two species, with spruce being less resistant to severe droughts when exposed to interaction with fir and beech; (iv) higher values of residual stand basal area following thinning were associated with lower resistance and resilience to severe droughts; and (v) larger trees were resilient to mild drought events but highly vulnerable to severe droughts. Our study provides an analytical approach for examining the effects of different factors on individual tree‐ and stand‐level drought response. The forests investigated here were to a certain extent resilient to mild droughts, and even benefited from such conditions, but were strongly affected by severe droughts. Lastly, negative effects of severe droughts can be reduced through modifying species composition, tree size distribution and stand density in mixed silver fir‐Norway spruce forests.

First U-Pb LA-ICP-MS in situ dating of supergene copper mineralization: case study in the Chuquicamata mining district, Atacama Desert, Chile - Zia Steven Kahou; Stéphanie Brichau; Marc Poujol; Stéphanie Duchêne; Eduardo Campos; Mathieu Leisen; François-Xavier d’Abzac; Rodrigo Riquelme; Sébastien Carretier (Mineralium Deposita, 2021)

Decreased duration of intravenous cephalosporins in intensive care unit patients with selective digestive decontamination: a retrospective before-and-after study - Calypso Mathieu; Roberta Abbate; Zoe Meresse; Emmanuelle Hammad; Gary Duclos; François Antonini; Nadim Cassir; Jeroen Schouten; Laurent Zieleskiewicz; Marc Leone (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Population, Temperature and Feeding Rate Effects on Individual Feed Efficiency in European Sea Bass (Dicentrarchus labrax) - Charles Rodde; Marc Vandeputte; François Allal; Mathieu Besson; Frédéric Clota; Alain Vergnet; John A. H. Benzie; Hugues de Verdal (Frontiers in Marine Science, 2020)

Distance sampling vs. plot sampling for monitoring population abundances of the Pyrenean rock ptarmigan - Gaël Aleix-Mata; Marc Mossoll-Torres; Evelyn Marty; Mathieu Boos; Antonio Sánchez; Jesús M. Pérez (European Journal of Wildlife Research, 2020)

Multiple glacial refugia and contemporary dispersal shape the genetic structure of an endemic amphibian from the Pyrenees - Federica Lucati; Manon Poignet; Alexandre Miró; Audrey Trochet; Fabien Aubret; Laurent Barthe; Romain Bertrand; Teresa Buchaca; Olivier Calvez; Jenny Caner; Elodie Darnet; Mathieu Denoël; et al. (Molecular Ecology, 2020)
Historical factors (colonization scenarios, demographic oscillations) and contemporary processes (population connectivity, current population size) largely contribute to shaping species’ present‐day genetic diversity and structure. In this study, we use a combination of mitochondrial and nuclear DNA markers to understand the role of Quaternary climatic oscillations and present‐day gene flow dynamics in determining the genetic diversity and structure of the newt Calotriton asper (Al. Dugès, 1852), endemic to the Pyrenees. Mitochondrial DNA did not show a clear phylogeographic pattern and presented low levels of variation. In contrast, microsatellites revealed five major genetic lineages with admixture patterns at their boundaries. Approximate Bayesian computation analyses and linear models indicated that the five lineages likely underwent separate evolutionary histories and can be tracked back to distinct glacial refugia. Lineage differentiation started around the Last Glacial Maximum at three focal areas (western, central and eastern Pyrenees) and extended through the end of the Last Glacial Period in the central Pyrenees, where it led to the formation of two more lineages. Our data revealed no evidence of recent dispersal between lineages, whereas borders likely represent zones of secondary contact following expansion from multiple refugia. Finally, we did not find genetic evidence of sex‐biased dispersal. This work highlights the importance of integrating past evolutionary processes and present‐day gene flow and dispersal dynamics, together with multilocus approaches, to gain insights into what shaped the current genetic attributes of amphibians living in montane habitats.

Identification of two new trichome-specific promoters of Nicotiana tabacum - Mathieu Pottier; Raphaëlle Laterre; Astrid Van Wessem; Aldana M. Ramirez; Xavier Herman; Marc Boutry; Charles Hachez (Planta, 2020)

Development of Surface Drifting Buoys for Fiducial Reference Measurements of Sea-Surface Temperature - Marc Le Menn; Paul Poli; Arnaud David; Jérôme Sagot; Marc Lucas; Anne O'Carroll; Mathieu Belbeoch; Kai Herklotz (Frontiers in Marine Science, 2019)

Sharing cells with Wolbachia : the transovarian vertical transmission of Culex pipiens densovirus - Mine Altinli; Julien Soms; Marc Ravallec; Fabienne Justy; Manon Bonneau; Mylene Weill; Anne‐Sophie Gosselin‐Grenet; Mathieu Sicard (Environmental Microbiology, 2019)
Summary Culex pipiens densovirus (CpDV), a single stranded DNA virus, has been isolated from Culex pipiens mosquitoes but differs from other mosquito densoviruses in terms of genome structure and sequence identity. Its transmission from host to host, the nature of its interactions with both its host and host's endosymbiotic bacteria Wolbachia are not known. Here, we report the presence of CpDV in the ovaries and eggs of Cx. pipiens mosquitoes in close encounters with Wolbachia . In the ovaries, CpDV amount significantly differed between mosquito lines harbouring different strains of Wolbachia and these differences were not linked to variations in Wolbachia densities. CpDV was vertically transmitted in all laboratory lines to 17%–20% of the offspring. For some females, however, the vertical transmission reached 90%. Antibiotic treatment that cured the host from Wolbachia significantly decreased both CpDV quantity and vertical transmission suggesting an impact of host microbiota, including Wolbachia, on CpDV transmission. Overall our results show that CpDV is transmitted vertically via transovarian path along with Wolbachia with which it shares the same cells. Our results are primordial to understand the dynamics of densovirus infection, their persistence and spread in populations considering their potential use in the regulation of mosquito vector populations.

Effects of Rht-B1 and Ppd-D1 loci on pollinator traits in wheat - Takashi Okada; J. E. A. Ridma M. Jayasinghe; Paul Eckermann; Nathan S. Watson-Haigh; Patricia Warner; Yonina Hendrikse; Mathieu Baes; Elise J. Tucker; Hamid Laga; Kenji Kato; Marc Albertsen; Petra Wolters; et al. (Theoretical and Applied Genetics, 2019)

The Copernicus Surface Velocity Platform drifter with Barometer and Reference Sensor for Temperature (SVP-BRST): genesis, design, and initial results - Paul Poli; Marc Lucas; Anne O'Carroll; Marc Le Menn; Arnaud David; Gary K. Corlett; Pierre Blouch; David Meldrum; Christopher J. Merchant; Mathieu Belbeoch; Kai Herklotz (Ocean Science, 2019)
To support calibration and validation of satellite sea surface temperature (SST) retrievals, over 60 high-resolution SST (HRSST) drifting buoys were deployed at sea between 2012 and 2017. Their data record is reviewed here. It is confirmed that sea state and immersion depth play an important role in understanding the data collected by such buoys and that the SST sensors need adequate insulation. In addition, calibration verification of three recovered drifters suggests that the sensor drift is low, albeit negative at around −0.01 K year−1. However, the statistical significance of these results is limited, and the calibration procedure could not be exactly reproduced, introducing additional uncertainties into this drift assessment. Based on lessons learnt from these initial buoys, a new sensor package for the Surface Velocity Platform with Barometer (SVP-B) was designed to serve calibration of SST retrievals by European Union's Copernicus satellites. The novel sensor package includes an HRSST sensor calibrated by a metrology laboratory. The sensor includes a pressure probe to monitor immersion depth in calm water and acquires SST data at 1 Hz over a 5 min interval every hour. This enables the derivation of mean SST as well as several percentiles of the SST distribution. The HRSST sensor is calibrated with an uncertainty better than 0.01 K. Analysis of the data collected by two prototypes deployed in the Mediterranean Sea shows that the buoys are able to capture small-scale SST variations. These variations are found to be smaller when the sea state is well mixed and when the buoys are located within eddy cores. This affects the drifter SST data representativeness, which is an aspect of importance for optimal use of these data.

Can one detect atrial fibrillation using a wrist-type photoplethysmographic device? - Sibylle Fallet; Mathieu Lemay; Philippe Renevey; Célestin Leupi; Etienne Pruvot; Jean-Marc Vesin (Medical & Biological Engineering & Computing, 2019)

Individual identification and marking techniques for zebrafish - Johann Delcourt; Michaël Ovidio; Mathieu Denoël; Marc Muller; Hélène Pendeville; Jean-Louis Deneubourg; Pascal Poncin (Reviews in Fish Biology and Fisheries, 2018)

Overall and differentiated sensory responses to cardiopulmonary exercise test in patients with cystic fibrosis: kinetics and ability to predict peak oxygen uptake - Mathieu Gruet; Laurent Mely; Jean-Marc Vallier (European Journal of Applied Physiology, 2018)

Contamination of soils by metals and organic micropollutants: case study of the Parisian conurbation - Johnny Gaspéri; Sophie Ayrault; Elodie Moreau-Guigon; Fabrice Alliot; Pierre Labadie; Hélène Budzinski; Martine Blanchard; Bogdan Muresan; Emilie Caupos; Mathieu Cladière; David Gateuille; Bruno Tassin; et al. (Environmental Science and Pollution Research, 2018)

High mobility group box 1 (HMGB1): dual functions in the cochlear auditory neurons in response to stress? - Sabine Ladrech; Jing Wang; Marc Mathieu; Jean-Luc Puel; Marc Lenoir (Histochemistry and Cell Biology, 2017)

Evaluation of Water Quality from Suburban Shallow Wells Under Tropical Conditions According to the Seasonal Variation, Bumbu, Kinshasa, Democratic Republic of the Congo - Michel L. Kapembo; Amandine Laffite; Mathieu K. Bokolo; Aimé L. Mbanga; Marc M. Maya-Vangua; Jean-Paul Otamonga; Crispin K. Mulaji; Pius T. Mpiana; Walter Wildi; John Poté (Exposure and Health, 2016)

Whose truffle is this? Distribution patterns of ectomycorrhizal fungal diversity in T uber melanosporum brûlés developed in multi‐host M editerranean plant communities - Elisa Taschen; Mathieu Sauve; Adrien Taudiere; Javier Parlade; Marc‐André Selosse; Franck Richard (Environmental Microbiology, 2015)
Summary In the M editerranean region, patches of vegetation recovering from disturbance and transiently dominated by shrubs produce one of the world's most prized fungi, the black truffle ( T uber melanosporum ). In these successional plant communities, we have fragmentary knowledge of the distribution of T . melanosporum in space among ectomycorrhizal ( ECM ) host species and in time. Molecular identification of hosts (Restriction Fragment Length Polymorphism) and fungi (Internal Transcribed Spacer sequencing) and quantification of T . melanosporum mycelium (quantitative Polymerase Chain Reaction) were employed to evaluate the presence of T . melanosporum on four dominant ECM host species ( Q uercus ilex , Q uercus coccifera , A rbutus unedo , C istus albidus ) and the extent to which their respective ECM communities shared fungal diversity, over the course of development of truffle grounds, from recent unproductive brûlés to senescent ones where production has stopped. We found that truffle grounds host rich communities in which multi‐host fungal species dominate in frequency. When considering both ECM tips and soil mycelia, we documented a dynamic and spatially heterogeneous pattern of T . melanosporum distribution in soils and a presence of ECM tips restricted to Q . ilex roots. This study advances our knowledge of the ecology of T . melanosporum , and provides insight into the extent of ECM fungal sharing among plant species that dominate M editerranean landscapes.

A predictive model based on a pluviothermic index for leathery pocket and fruitlet core rot of pineapple cv. ‘Queen’ - Patrick Fournier; Aurore Benneveau; Christelle Hardy; Marc Chillet; Mathieu Léchaudel (European Journal of Plant Pathology, 2015)

Investigating the Neural Correlates of the Stroop Effect with Magnetoencephalography - Sophie Galer; Marc Op De Beeck; Charline Urbain; Mathieu Bourguignon; Noémie Ligot; Vincent Wens; Brice Marty; Patrick Van Bogaert; Philippe Peigneux; Xavier De Tiège (Brain Topography, 2015)

Occurrence of 1,1′-dimethyl-4,4′-bipyridinium (Paraquat) in irrigated soil of the Lake Chad Basin, Niger - Marc Crampon; Yoann Copard; Guillaume Favreau; Julie Raux; Nadine Merlet-Machour; Mathieu Le Coz; Maïmouna Ibrahim; Valérie Peulon-Agasse; Florence Portet-Koltalo (Environmental Science and Pollution Research, 2014)

Inter- and Intra-Subject Variability of Neuromagnetic Resting State Networks - Vincent Wens; Mathieu Bourguignon; Serge Goldman; Brice Marty; Marc Op de Beeck; Catherine Clumeck; Alison Mary; Philippe Peigneux; Patrick Van Bogaert; Matthew J. Brookes; Xavier De Tiège (Brain Topography, 2014)

Comprehensive Functional Mapping Scheme for Non-Invasive Primary Sensorimotor Cortex Mapping - Mathieu Bourguignon; Veikko Jousmäki; Brice Marty; Vincent Wens; Marc Op de Beeck; Patrick Van Bogaert; Mustapha Nouali; Thierry Metens; Boris Lubicz; Florence Lefranc; Michael Bruneau; Olivier De Witte; et al. (Brain Topography, 2013)

Precipitation and temperature space–time variability and extremes in the Mediterranean region: evaluation of dynamical and statistical downscaling methods - Emmanouil Flaounas; Philippe Drobinski; Mathieu Vrac; Sophie Bastin; Cindy Lebeaupin-Brossier; Marc Stéfanon; Marco Borga; Jean-Christophe Calvet (Climate Dynamics, 2013)

Video multitracking of fish behaviour: a synthesis and future perspectives - Johann Delcourt; Mathieu Denoël; Marc Ylieff; Pascal Poncin (Fish and Fisheries, 2013)
With the development of digital imaging techniques over the last decade, there are now new opportunities to study complex behavioural patterns in fish (e.g. schooling behaviour) and to track a very large number of individuals. These new technologies and methods provide valuable information to fundamental and applied science disciplines such as ethology, animal sociology, animal psychology, veterinary sciences, animal welfare sciences, statistical physics, pharmacology as well as neuro‐ and ecotoxicology. This paper presents a review of fish video multitracking techniques. It describes the possibilities of tracking individuals and groups at different scales, but also outlines the advantages and limitations of the detection methods. The problem of occlusions, during which errors of individual identifications are very frequent, is underlined. This paper summarizes different approaches to improving the quality of individual identification, notably by the development of three‐dimensional tracking, image analysis and probabilistic applications. Finally, implications for fish research and future directions are presented.

On the canopy structure manipulation to buffer climate change effects on insect herbivore development - Marc Saudreau; Sylvain Pincebourde; Mathieu Dassot; Boris Adam; Hugh D. Loxdale; David G. Biron (Trees, 2013)

The effects of snowpack properties and plant strategies on litter decomposition during winter in subalpine meadows - Patrick Saccone; Samuel Morin; Florence Baptist; Jean-Marc Bonneville; Marie-Pascale Colace; Florent Domine; Mathieu Faure; Roberto Geremia; Jonathan Lochet; Franck Poly; Sandra Lavorel; Jean-Christophe Clément (Plant and Soil, 2013)

Engineering of a phosphorylatable tag for specific protein binding on zirconium phosphonate based microarrays - Mathieu Cinier; Marc Petit; Frédéric Pecorari; Daniel R. Talham; Bruno Bujoli; Charles Tellier (JBIC Journal of Biological Inorganic Chemistry, 2012)

Expression of the Beet necrotic yellow vein virus p25 protein induces hormonal changes and a root branching phenotype in Arabidopsis thaliana - Claire Peltier; Laure Schmidlin; Elodie Klein; Ludivine Taconnat; Els Prinsen; Mathieu Erhardt; Dimitri Heintz; Guy Weyens; Marc Lefebvre; Jean-Pierre Renou; David Gilmer (Transgenic Research, 2011)

Adaptative modifications of right coronary myocytes voltage-gated K+ currents in rat with hypoxic pulmonary hypertension - Jean-Marc Hyvelin; Mathieu Gautier; Marie-Christine Lemaire; Pierre Bonnet; Véronique Eder (Pflügers Archiv - European Journal of Physiology, 2009)

Characterization of a putative type IV aminophospholipid transporter P-type ATPase - Stéphane Flamant; Pascale Pescher; Brigitte Lemercier; Mathieu Clément-Ziza; François Képès; Marc Fellous; Geneviève Milon; Gilles Marchal; Claude Besmond (Mammalian Genome, 2003)

Overexpression of the human glucocorticoid receptor α and β isoforms inhibits AP-1 and NF-κB activities hormone independently - Claire Gougat; Dany Jaffuel; Rosalia Gagliardo; Corinne Henriquet; Jean Bousquet; Pascal Demoly; Marc Mathieu (Journal of Molecular Medicine, 2002)

The South Eastern Durance fault permanent network: Preliminary results - Philippe Volant; Catherine Berge-Thierry; Pierre Dervin; Marc Cushing; Georgianna Mohammadioun; Franck Mathieu (Journal of Seismology, 2000)

Engineering of zinc finger and MHC motifs to locked-in tertiary folds - Marc Mathieu; Christian Lehmann; Alain Razaname; Gabriele Tuchscherer (International Journal of Peptide Research and Therapeutics, 1997)